2004
DOI: 10.1111/j.1445-5994.2004.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards more effective use of decision support in clinical practice: what the guidelines for guidelines don’t tell you

Abstract: The Brisbane Cardiac Consortium Clinical Support Systems Program used multiple strategies in optimising quality of care of patients with either of two cardiac conditions. One of these strategies was the development and active implementation of decision support systems centred on evidence-based, locally agreed clinical practice guidelines. Our experience in undertaking this task highlighted numerous operational challenges for which solutions were difficult to extract from existing published literature. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 69 publications
1
22
0
4
Order By: Relevance
“…The results of this study support previous research that identified that guideline formats and content are important determinants of usability of guidelines in busy clinical environments such as the emergency care sector [11-13]. A survey of multidisciplinary clinicians in Australian public hospitals reported that concise, quick-reference formats were preferred to detailed texts (35% vs. 6%; P < 0.001) [12-14].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study support previous research that identified that guideline formats and content are important determinants of usability of guidelines in busy clinical environments such as the emergency care sector [11-13]. A survey of multidisciplinary clinicians in Australian public hospitals reported that concise, quick-reference formats were preferred to detailed texts (35% vs. 6%; P < 0.001) [12-14].…”
Section: Discussionsupporting
confidence: 83%
“…This study revealed that 66% of the respondents were unfamiliar with the GRADE system for rating the quality of evidence and recommendations. This is supported by Kotzeva et al [13-15], who reported that clinicians had limited knowledge, experience and understanding of GRADE. This knowledge deficit related to the grading of recommendations is potentially important as a reflection of respondent capacity to recognize and critically evaluate the approach to rating the strength of evidence used by recently developed guidelines.…”
Section: Discussionmentioning
confidence: 72%
“…This is an important message for overcoming possible barriers in implementation of the EBMeDS in a multi-profession context. An Australian study [56] also found that education of professionals and motivation of multidisciplinary groups to redesign care processes can aid in overcoming potential barriers to implementation. In addition, our results reaffirm that needs of nurses and other professionals have to be carefully targeted in the development of automatic reminders for those specific groups [57].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the above, a predominant focus on catastrophic but infrequent harm and ‘near misses’ that are directly attributable to errors of task execution ignores a much greater reservoir of potential iatrogenesis. Narrowing gaps between best practice and routine care by deploying effective systems of clinical decision support, practice evaluation and care improvement (Table 5) may realize much larger dividends in improved patient outcomes than relying solely on administrative instruments such as sentinel event reporting or risk registers 48–52 …”
Section: Time To Reconsider Basic Tenetsmentioning
confidence: 99%